2013
DOI: 10.1002/chem.201302200
|View full text |Cite
|
Sign up to set email alerts
|

Organogelation‐Controlled Topochemical [2+2] Cycloaddition and Morphological Changes: From Nanofiber to Peculiar Coaxial Hollow Toruloid‐Like Nanostructures

Abstract: Novel amphiphilic molecules composed of naphthylacryl and L-glutamide moieties (1-NA and 2-NA) have been designed and their organogel formation in various organic solvents as well as their self-assembled nanostructures have been investigated. Both compounds formed organogels in many organic solvents, ranging from nonpolar to polar, and self-assembled into essentially nanofiber structures, although some twist or belt structures could be observed in certain solvents. A gel of compound 2-NA in ethanol initially s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 74 publications
4
27
0
Order By: Relevance
“…The corresponding distances were estimated to be 5.4, 2.7, 1.84 nm and so on according to the Bragg's equation. The d -spacing ratio is about 1:1/2:1/3, which is consistent with the characteristic of lamellar packing of the molecules47. As for L-1/BPEA, the XRD pattern was identical to the one of pure L-1, which confirmed that the addition of BPEA to L-1 did not destroy the well-ordered packing of L-1.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The corresponding distances were estimated to be 5.4, 2.7, 1.84 nm and so on according to the Bragg's equation. The d -spacing ratio is about 1:1/2:1/3, which is consistent with the characteristic of lamellar packing of the molecules47. As for L-1/BPEA, the XRD pattern was identical to the one of pure L-1, which confirmed that the addition of BPEA to L-1 did not destroy the well-ordered packing of L-1.…”
Section: Resultssupporting
confidence: 78%
“…As shown in Supplementary Fig. 11b, the appearance of an N–H stretching vibration band at 3,296 cm −1 for L-1 xerogel indicated the formation of the hydrogen bond47. The amide I band and II band appeared at 1,638 cm −1 and 1,553 cm −1 , respectively, which indicates that both C=O and N–H are in the hydrogen-bonded form.…”
Section: Resultsmentioning
confidence: 78%
“…The N−H and C=O stretching bands in powder GO were positioned at 3371 and 1731 cm −1 and shifted to 3269 and 1721 cm −1 , respectively, in the DMF gel (Figure S6 c). Here, the carbonyl is similar to a carbamate, not a typical amide for which the stretching frequency is in the range of 1720 to 1660 cm −1 according to the strength of hydrogen bonding . The carbonyl stretching frequency was found in the range of 1700 to 1710 cm −1 , which indicated the formation of weak intermolecular hydrogen bonds in the self‐assembly system.…”
Section: Resultsmentioning
confidence: 81%
“…Here, the carbonyl is similart oac arbamate, not at ypical amide for which the stretching frequency is in the range of 1720 to 1660 cm À1 according to the strength of hydrogen bonding. [74,79,80] The carbonyl stretching frequency was found in the range of 1700 to 1710 cm À1 ,w hich indicated the formation of weak intermolecular hydrogen bondsi nt he self-assembly system.…”
Section: Resultsmentioning
confidence: 98%
“…A remarkable study by Wang et al demonstrated that nonuniformity in the product distribution can cause a fibrous gel aggregate to fragment into various intricately defined toroidal structures. 301 The reaction involves the [2+2] cycloaddition of a naphthylacryl-functionalised dialkylglutamide, and is thought to produce hollow architectures due to expansion of the material as the coupling proceeds. The monomer may be recovered through thermal dissolution of the product aggregate, and is rendered unreactive if self-assembly occurs in a solvent other than methanol or ethanol, due to slight differences in the packing of naphthylacryl moieties.…”
Section: Coupling Reactionsmentioning
confidence: 99%